Public Health Graduates' Perceptions of the Educational Environment Measured by the DREEM - Xu, Fang-Rong; Yang, Yang (Frontiers in Public Health, 2022)
Objective Students' perceptions of the educational environment have a significant impact on their behavior and academic progress. This study aims to measure medical graduates' perception of the educational environment within the School of Public Health at Wuhan University in China. Methods The survey was conducted by emails sent to 119 graduates, and 93 valid questionnaires were returned. The DREEM was used to assess the medical graduates' satisfaction with the educational environment. Results The average score on the scale was 126.02 (±18.27). The scoring rate of the areas ranged between 61.06 and 67.11%. The area with the highest score was “perception of teachers.” The area with the lowest score was “academic self-perception.” No difference was found between genders. Except for “perception of atmosphere,” the total scores and other areas showed differences in graduation time. Conclusion The educational environment at the School of Public Health at Wuhan University was satisfactory. The program contributed to the graduates' later careers. The information obtained in this study identified some areas for improvement.